2011
DOI: 10.1186/1742-2094-8-64
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia (bitter melon) attenuates high-fat diet-associated oxidative stress and neuroinflammation

Abstract: BackgroundThe rising epidemic of obesity is associated with cognitive decline and is considered as one of the major risk factors for neurodegenerative diseases. Neuroinflammation is a critical component in the progression of several neurological and neurodegenerative diseases. Increased metabolic flux to the brain during overnutrition and obesity can orchestrate stress response, blood-brain barrier (BBB) disruption, recruitment of inflammatory immune cells from peripheral blood and microglial cells activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 70 publications
5
78
0
1
Order By: Relevance
“…Therefore, we had targeted the effects of MC on TBARS, GSH, MPO, TNFalpha and IL 6 levels. Our results showed that the pretreatment with MC restored the depletion of GSH, along with a decrease of the augmented levels of TBARS, MPO, TNF-alpha and IL 6 due to vincristine administration and were in line with earlier reports (Kobori et al, 2008;Lii et al, 2009;Kenny et al, 2013;Nerurkar et al, 2011). The protective effect of MC may be attributed to the presence of bioactive compounds, which may be responsible for quenching of free radicals, or alternatively, it may be due to the up-regulation of antioxidant and anti-inflammatory systems.…”
Section: Protective Effect Of Standardized MC In Vincristine Inducedsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, we had targeted the effects of MC on TBARS, GSH, MPO, TNFalpha and IL 6 levels. Our results showed that the pretreatment with MC restored the depletion of GSH, along with a decrease of the augmented levels of TBARS, MPO, TNF-alpha and IL 6 due to vincristine administration and were in line with earlier reports (Kobori et al, 2008;Lii et al, 2009;Kenny et al, 2013;Nerurkar et al, 2011). The protective effect of MC may be attributed to the presence of bioactive compounds, which may be responsible for quenching of free radicals, or alternatively, it may be due to the up-regulation of antioxidant and anti-inflammatory systems.…”
Section: Protective Effect Of Standardized MC In Vincristine Inducedsupporting
confidence: 94%
“…Earlier, oil extracted from the seed of MC, when applied topically to the patients of spondylitis, rheumatoid arthritis and diabetic neuropathy demonstrated relief from pain (Pushpa Khanna, 2005). Moreover, study done by Nerurkar et al (2011) showed that the methanolic extract of bitter melon fruit [catechin (3% w/w), quercetin (0.62% w/w), trans-chalone (0.3% w/w), caffeine (0.25% w/w); while, GA, caffeic acid, and flavones (less than 0.01% w/w) in BM methanolic extracts] lowers the expression of neuro-inflammatory markers such as NF-κB1, IL-16, IL-22 as well as IL-17R in the brains of mice fed with high-fat diet. Further MC fruit extract showed relief from acetic acid induced writhing pain in rats (Ullah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Various extracts of bitter gourd have potential antioxidant activity which might play an important role in diabetic-related enzymes and individuals with neuroinflammation and liver diseases. Nerurkar et al [67] reported that the administration of bitter melon fruit extract significantly reduced the neurodegenerative diseases as its role as antioxidant to reveal a mechanism for its neuroinflammation action. Cucurbitane-type triterpene glycoside 1 and 3 isolated from stems and fruits of M. charantia significantly inhibit the effect on Xanthine oxidase activity which is the key enzyme for the induction hyperuricemia and gout [68].…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…Most studies support the notion that HFD increases BBB permeability. In some, HFD‐induced changes in BBB permeability were evident by increased leakage of Evans blue dye in 16‐week‐old mice brain (Nerurkar et al, 2011). In others, obesity exacerbated early postischemic BBB disruption in 16‐week‐old mice fed HFD.…”
Section: Introductionmentioning
confidence: 99%